(untitled) (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2024)
EFFECT OF COMBINING ORGANIC FERTILIZER AND INORGANIC FERTILIZER IN F1 HYBRID SWEET CORN CULTIVATION IN SPRING-SUMMER CROP IN ALLUVIAL LAND COVERED WITH SEA SAND IN TRA VINH PROVINCE, VIETNAM Tóm tắt: Nghiên cứu xác định loại bắp ngọt (Zea mays L. var. rugosa) F1 và phân hữu cơ phù hợp cho đất phù sa phủ trên nền cát biển (Areni Dystric Fluvisols) tại tỉnh Trà Vinh. Thí nghiệm thực hiện trên hai giống bắp Min 5 và Golden Cob được bón năm loại phân hữu cơ kết hợp phân vô cơ: 120 N–60 P2O5-60 K2O (kg/ha). Kết quả chỉ ra, giống bắp Golden Cob có chiều cao cây, chiều cao đóng trái, diện tích lá đóng trái, đường kính trái và khối lượng (P.1000 hạt) có sự sai khác so với giống bắp Min 5. Ba loại phân hữu cơ có hiệu quả lên chiều cao đóng trái bắp, đường kính gốc và khối lượng P.1000 hạt là phân khoáng, phân trùn quế và phân vi sinh Siamb Soyamin. Trong đó, giống bắp Min 5 kết hợp bón phân hữu cơ khoáng có khối lượng P.1000 hạt là 582,14 g, giống bắp Golden Cob bón phân trùn quế và phân vi sinh Siamb Soyamin thì khối lượng P.1000 hạt gần như nhau lần lượt là 523,78 g và 518,45 g. Năng suất thực thu của nghiệm thức Min 5 và Golden Cob bón phân vi sinh Siamb Soyamin đạt 5,615 tấn/ha và 5,591 tấn/ha, cao hơn các nghiệm thức còn lại. Abstract: The study aimed to find suitable sweet corn (Zea mays L. var. rugosa) F1 and organic fertilizer for Areni Dystric Fluvisols in Tra Vinh Province, Vietnam. The experiment was conducted on two corn varieties, Min 5 and Golden Cob, fertilized with five types of organic and inorganic fertilizers: 120 N–60 P2O5-60 K2O (kg/ha). The results showed that the Golden Cob corn variety had differences in plant height, ear height, leaf area, ear diameter and weight of P.1000 grains compared to the Min 5 corn variety. The three types of compost that are effective in increasing the ear height, stump diameter and grain volume P.1000 are mineral manure, vermicompost and Siamb Soyamin microbial fertilizer. Specifically, the Min 5 corn variety cultivated with mineral organic fertilizer achieved P.1000 grain weight is 582.14 g. In comparison, the Golden Cob corn variety treated with vermicompost and Siamb Soyamin microbial fertilizer achieved almost the same P.1000 grain weight of 523.78 g and 518.45 g, respectively. The actual yield of Min 5 and Golden Cob treatments with Siamb Soyamin microbial fertilizer reached 5.615 tons/ha and 5.591 tons/ha, higher than the other treatments.